Anticoagulation with rivaroxaban: covering a broad spectrum of thromboembolic disease. (July 2013) - Schellong, Sebastian
Traditional anticoagulants such as heparin and vitamin K antagonists have been the mainstay of antithrombotic therapy for many years. However, these drugs have a number of well-recognized drawbacks: unfractionated heparin, low molecular weight heparins and fondaparinux are administered parenterally, and vitamin K antagonists require routine coagulation monitoring. Novel, single-target oral anticoagulants have been developed that do not need routine coagulation monitoring, including the direct factor Xa inhibitors rivaroxaban, apixaban and edoxaban, and the direct thrombin inhibitor dabigatran. Rivaroxaban is the most advanced in its clinical development. Across all ten Phase III/IV trials, rivaroxaban met the primary efficacy end points and generally had similar incidences of bleeding, with a comparable safety profile to standard-of-care.